Estudo de fase clínica I utilizando membrana de quitosana dopada com hormônios derivados de plaquetas - Ferreira, Simone Da Silva [UNESP] (2014)
Chronic wounds (CW are a constant challenge for pharmaceutical companies. The Blood Center of Botucatu develops products formulated 13 years ago from Fresh Plasma and platelets concentrate excess clinical practice. One of these products is well established and tested laminar platelet gel (Biogel/PG). Research in nursing identified opportunities for improvements to the Biogel/PG being proposed new wording: chitosan membrane enriched with platelet hormones (Quitogel). After preliminary studies have outlined the design of a phase I study in patients with CF using the Quitogel compared with Biogel/GP. This is a prospective, controlled clinical trial type, and aimed to compare the performance of the chitosan membrane doped with hormones versus Biogel/PG establishing the profile of patients seen. The past 24 months were served 135 new cases of CW, 45 male, mean age of 49.57 years and the time of open wound was 87.57 months. Females were 90 cases, with a mean age of 52.91 years and mean duration of open wound was 114.76 months. Regarding the type of ulcer, 81% were venous for women versus 64% for men. Chronic traumatic injuries (9%) were more prevalent in men, compared with 2% in women and diabetic wounds hit men (11%) more. Of marketed products most used by patients, include collagenase (16%), silver sulfadiazine (12%), fibrase ® (10%), papain (6%), Safgel ® (5%), 5% hydrogels. High rate of self-medication, a fact, compromising the outcome of the treatment of CW, where 33 (44.55%), was identified patients had reported having a prescribed product, but use the other 2 did not prescribed. Of these 135 patients, 27 of them participated in the study, a total of 31 lesions that were followed for 90 days. Comparison of the two products (Biogel/GP versus Quitogel), it was observed that in the preparation of doped chitosan membrane is easy storage (room temperature) and hydration with saline, gradually releases the hormones platelet does not favor ...